IMPLEMENTATION OF ENTERPRISE RESOURCE PLANNING (ERP) IN THE WAREHOUSE DIVISION - Agus Sulaksono; Hadir Hudiyanto; Julius Nursyamsi (International Journal Multidisciplinary Science, 2023)
Enterprise Resources Planning (ERP) is an integrated system that covers all business functions contained in a company and is driven by several integrated software modules to support the company's internal business processes. PT Z, an F&B company, intends to implement an ERP system in its warehouse division to support its business activities. The purpose of this research is to design an ERP system in the company's warehouse division. The research begins with business process data and historical data collection. A system analysis is then carried out to identify and model the warehouse division's business processes. From the business process model created, use case diagrams and class diagrams are then made to compile the contextual framework of the ERP system. The ERP system was then developed with Odoo 16's inventory module. The ERP system designed and implemented is in accordance with the results of the analysis and can be used according to existing business processes.